Comparative Study of Fuzzy Logic Based Speed Control of Multilevel Inverter fed Brushless DC Motor Drive - Pritha Agrawal; Satya Prakash Dubey; Satyadharma Bharti (Institute of Advanced Engineering and Science, 2014)
This paper presents a comparative analysis of speed control of brushless DC motor (BLDC) drive fed with conventional two-level, three and five level diode clamped multilevel inverter (DC-MLI). The performance of the drive system is successfully evaluated using Fuzzy Logic (FL) based speed controller. The control structure of the proposed drive system is described. The speed and torque characteristic of conventional two-level inverter is compared with the three and five-level multilevel inverter (MLI) for various operating conditions. The three and five level diode clamped multilevel inverters are simulated using IGBT’s and the mathematical model of BLDC motor has been developed in MATLAB/SIMULINK environment. The simulation results show that the Fuzzy based speed controller eliminate torque ripples and provides fast speed response. The developed Fuzzy Logic model has the ability to learn instantaneously and adapt its own controller parameters based on disturbances with minimum steady state error, overshoot and rise time of the output voltage.DOI: http://dx.doi.org/10.11591/ijpeds.v4i1.4745